Thermostabilization of live Newcastle disease virus (La Sota) Thermostabilization of live Newcastle disease virus (La Sota) - GANDGE, RAJASHREE; LONDHE, S P; SHERIKAR, A A (The Indian Journal of Animal Sciences, 2012)
The thermostability of NDV vaccine was studied by reconstituting commercially available vaccine with diluents prepared in H2O and 80% D2O at ambient temperature during summer and winter. The loss in vaccine potency due to inactivation of virus was studied in vitro using haemagglutination test at various time intervals up to 50 and 203 h in summer and winter, respectively. Diluent prepared in 80% D2O when used for reconstitution of freeze-dried Ranikhet disease vaccine, it maintained stability of vaccine virus for more than 50 h during both summer and winter. The findings revealed that, freeze-dried NDV vaccine reconstituted in 80% D2O diluent can be used up to 50 h or more at 35°C ± 2°C temperatures without any deterioration in potency.